PENERAPAN TERAPI PIJAT REFLEKSI KAKI LANSIA PENDERITA DIABETES MELLITUS DI PANTI BUDI SOSIAL - Zullia Agustia Wati; Afif D Alba (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Type 2 Diabetes Mellitus is a chronic disease characterized by elevated blood glucose levels resulting from insulin resistance or inadequate insulin production. One of the interventions to address increased blood glucose levels is reflexology massage therapy, a complementary therapy that serves as an alternative treatment approach. Reflexology massage therapy is a complementary intervention that integrates various nursing techniques, including relaxation, touch, and distraction techniques. The purpose of this study was to provide gerontological nursing care, a patient with Type 2 Diabetes Mellitus, through the application of foot reflexology massage therapy at Panti Werda Budi Sosial, Batam City. The method was a case study encompassing nursing diagnosis, intervention, implementation, and evaluation. The results of the case study revealed a reduction in the patient’s blood glucose levels. After receiving foot reflexology massage therapy for three sessions of 30 minutes each over three consecutive mornings, the patient’s blood glucose levels decreased from 203 mg/dL on the first day, to 190 mg/dL on the second day, and 162 mg/dL on the third day. These findings indicate that foot reflexology massage therapy has a significant effect on lowering blood glucose levels and alleviating acute foot pain in patients with Type 2 Diabetes Mellitus.Keywords: Diabetes Mellitus Type II, Elderly, Foot Reflexology Massage